PtSe2 and black phosphorus employed for sensitivity improvement in the surface plasmon resonance sensor - Karki, Bhishma; Ansari, Gufranullah; Uniyal, Arun; Srivastava, Vivek (Journal of computational electronics, 2023)
The analysis aims to enhance the sensitivity of the surface plasmon resonance-based sensor. The proposed sensor consists of a single layer of Ag metal, black phosphorus (BP), and Platinum diselenide (PtSe 2 ). The thickness of the Ag metal is considered as 45 nm. The study was carried out using attenuated total reflection. The refractive index of the sensor changes when analyte or biomolecules comes in contact with the sensing layer. The thickness of the BP layer has been taken as 0.34 nm. The maximum sensitivity of the sensor is achieved for one layer of PtSe 2 and two layers of BP. The calculated performance parameters, sensitivity, figure of merit, and detection accuracy, are 275.2 Degree / RIU , 43.1 RIU - 1 , and 0.16 Degree - 1 , respectively. The sensitivity of the proposed sensor is 1.38 times the conventional sensor.